PROBLEMATIQUE DE LA SUPPRESSION DE L’AUTORISATION MARITALE EN REPUBLIQUE DEMOCRATIQUE DU CONGO AU REGARD DE LA LOI N° 16/008 DU 16 JUILLET 2016 MODIFIANT ET COMPLETANT LA LOI N° 87-010 DU 1ER AOUT 1987 PORTANT LE CODE DE LA FAMILLE. Cas de la femme congol - MBIYE, Ibrahim KATHY (IJRDO - Journal of Social Science and Humanities Research, 2021)
Since its accession with independence, the Democratic Republic of Congo provides efforts and legal opportunities with the men and the women for their protection and safety.However, much remains to be made in order to allow the women to reach, in a sufficient number, with the authorities of decision-making. Inequalities of the rights, chance and sex persist between the men and women and make lose for the Democratic Republic of Congo, the useful contribution of the women for the achievement of its objectives of durable human development. This persistence of the disparities between men and women is noted in almost all the fields of the national life, particularly in the field political, economic, social and cultural. Disparities which entrainment, ineluctably, of discriminations blocking implementation the adequate of the parity man and woman.In front of this situation, the legal capacity of married woman is limited by the code of the family and the work in an excessive and discriminatory way by subjecting any act, posed by it, with the husband's permission.The same law on the women's rights and the parity promoted the dialogue and mutual protection instead of the husband's permission. Taken in accordance with article 40 of the constitution, it is also inspired by the treaties and international agreements ratified for the Democratic Republic by Congo as regards the basic rights.